PENGUKURAN KUALITAS WEBSITE RUMAH BATIK ANDALAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS - Siti Monalisa; Khairul Rizky (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Rumah Batik Andalan is a shop that produces Malay batik with the name of the mainstay batik home website. The website has never been evaluated on the quality of the website so there is no known level of website quality on visitor satisfaction. Webqual 4.0 method website problems on the Usability dimension regarding unattractive appearance, the Information Quality dimension is not updated in batik motifs, the Interaction Quality dimension does not have a sale and purchase transaction feature. The purpose of this study was to analyze website quality using the Webqual 4.0 method and Importance Performance Analysis (IPA). This research uses a quantitative approach by distributing questionnaires to visitors. The tools used to process data from questionnaires on WebQual and IPA are SPSS 22. The results of the analysis of the suitability level are still below 100% and the attributes are low with a value of 48%, which is quite detailed and safe information when transacting. all indicators, this shows that the quality of the website otherwise can not meet the wishes of users. While the results of the IPA analysis show that the priority indicators for improvement on the website are an attractive appearance, provide detailed information, and are safe when making transactions. The results of the calculation of the level of user satisfaction from the Customer Satification Index (CSI) on the Rumah Batik Andalan website obtained a value of 65%, this shows that the overall website performance was quite satisfied